Telemedicine Diffusion in a Developing Country: A case of Senegal - Femi Ekanoye; Foluso Emmanuel Ayeni; Temitope Olokunde; Vekima Nina; Carole Donalds; Victor Mbarika (International Journal of Computing and Informatics (IJCANDI), 2017)
Senegal is located in West Africa where health care resources are extremely limited. Although it is improving each day, many say that an even bigger improvement is needed to decrease the high mortality rate, and ensure good health countrywide. Several factors justify the efficient application of Telemedicine in Sub-Saharan Africa (SSA)  to augment the declining health care delivery system in that region of the world. In doing research, telemedicine, along with other solutions, play a huge role in ensuring this plan is effective because of its convenience and benefits. In recent years, the use of telemedicine has become increasingly popular in countries like Senegal. Telemedicine is significant because of its ability to transmit the needed information promptly. Besides, it is a means to communicate and care for patients having limited access to health care at efficient and personalized level. Over the years, the use of telemedicine has extended to several countries and the technology continues to improve each day.